De Levendes Land - Egebak, Niels (Grundtvig-Studier, 1970)
De Levendes Land (The Land of the Living). An interpretation By Niels Egebak By way of introduction this analysis (which has also appeared in a book of readings on the poem) assumes that the cultural and literary complex of problems in which the poem belongs should be looked upon as a text, to which the hymn under consideration bears an intertextual relationship. The biographical and psychological data relevant to the text, on the other hand, only acquire the status of text in the poem “de Levendes Land”; therefore they should be considered in the light of the poem, and not vice versa. The structure of the poem reveals the covert process that opposes it to Kingo’s hymn “Far, Verden, far vel” (a farewell to the world). By making the final stanza appear as the initial stanza in a later version Grundtvig admits its strategic significance. The two main sections of the poem consist of four smaller subtexts with the mutual relationships ABGD, each consisting of three stanzas: A depicts a land beyond time, whereas B dismisses this dream, C: the lost Paradise is regained here and now through the Christian faith, which, although it does not disown human nature, does not deify or idealise it. D: hope, reborn and confirmed in baptism, makes possible the realisation of the dream of Paradise through love emanating from above. E: the last stanza points out what makes this possible: Christianity with its message of love which applies both in heaven and on earth—that is, even “when the eye is blue”. It is asserted that in the poem there is a direct connection between Grundtvig’s settlement with Kingo and his settlement with romanticism. The first main section is a parody on Kingo’s conceptual universe; in the second main section he is taken to task: his attempt to describe blessedness through wordly values is rejected with contempt, whereas the romantic conception of childlike naivete as the way of admission to the lost Paradise is repeated in the text in the prayer to “Kærligheds Aand” (spirit of charity) (st. 7 ), echoing the Christian commandment that »Whosoever shall not receive the kingdom of God as a little child, he shall not enter therein”. The possibility that poetry “med Mund og Pen” (with mouth and pen) might restore the dream of Paradise is rejected: Nothing but a reflection, a likeness will come out of it (st. 5 ). Nevertheless, the poem itself is such a likeness, anticipated already in the poem “Nyaars-Morgen” (New Year’s Morning). Grundtvig must have wished to face the inevitability of death, live through the loss of an eternal life in a wordly sense, and then return without having become an unhappy man.—A comparison with “O Christelighed ’’shows that the word “I” has an important position in the original poem as compared to “we” in the rewritten version. C differs from the other three subtexts in that the textual sequence is reverse to the logical sequence. This inversion has the effect that the entire section 2 may be read as an inversion of section 1, which fact seems to have some bearing on what the text says about the relationship between romanticism and Christianity. The innocence we have lost may be regained through baptism, poetry gains power from a spark of the spirit of God, in Christian hymns the likeness becomes a hope that brings happiness, where the dream brought only grief and distress—this point is elucidated by a comparison of st. 4 and st. 10. In the poem we see a tension between two philosophies of life, romanticism and Christianity, an as yet unsettled struggle between an established ideology (romanticism) and an ideology that is still trying to find its proper course (Grundtvigianism). In the rewritten version “O Christelighed” the Grundtvigian ideology has become established. This, however, did not make Grundtvig a greater poet.